Maternal, fetal and new born outcomes in pre-eclampsia and eclampsia: a hospital based study (Health Renaissance, 2015)
Background: Pre-eclampsia /Eclampsia are becoming a leading cause of maternal and neonatal morbidity and mortality in developed and developing countries. Developing countries are at higher risk of facing this problem.Objective: To assess the maternal, fetal / newborn outcome of pre-eclampsia and eclampsia among mothers admitted in maternity ward of BPKIHS. Methods: This is a hospital based cross sectional study carried out in maternity ward at BPKIHS. A total 150 pregnant women (diagnosed of preeclampsia/eclampsia cases-75 and controls -75) included using purposive sampling technique. Data was collected using self-developed pretested, semi structured performa by the interview. Detailed physical examination and observations were also done. Results: Preterm delivery, early rupture of membrane, need for an assisted vaginal delivery (vacuum and forceps) and caesarean delivery, were significantly higher in cases than controls (P < 0.001). Abnormal range of fetal heart rate, still birth, intrauterine fetal death, birth asphyxia ,need for resuscitation, low birth weight and intrauterine growth retardation were significantly higher in cases than controls (P